Classification of Methods to Reduce the Carbon Footprint - KEMPA, Filip (GeoScience Engineering, 2023)
The ever-increasing amount of greenhouse gases in the atmosphere has an adverse impact on the environment, causing global warming and related adverse effects. One of the most important greenhouse gases is carbon dioxide, the production of which is perceived as a carbon footprint. The carbon footprint is intended to be a tool for appropriate emission reductions and verification, so there is a great need for its standardization at the global level. In carrying out basic research and after working out the advantages and disadvantages, many methods of decarbonization have been identified. The author believes that by simplifying the classification of carbon footprint reduction approaches into appropriate classes, a clear tool guiding companies in decarbonizing their operations will be created so that the negative impacts of global warming on the Earth are averted as quickly as possible. The aim is, therefore, to identify similarities and differences in methods, which will lead to the identification of new main groups of approaches. Within the framework of the evaluation and after making a comparison according to selected aspects of intensity, seven basic approaches have emerged, thus achieving greater clarity, usability, and better orientation for companies on the issue of reducing their carbon footprint. The results are illustrated at the end of the paper. The least challenging method for low-carbon technology adoption is the promotion of education and dissemination of climate impact awareness. Conversely, the most challenging method appears to be the construction of new green buildings. Keywords: Advantages; Carbon footprint; Classification of ways; Comparison; Disadvantages.